Perancangan Sistem Informasi Pelayanan Pasien Rawat Jalan dan Rawat Inap pada Rumah Bersalin dan Klinik Gebang Medika - Hapsari Widyani (Neolectura, 2020)
The purpose of this study was to analyze the processes and procedures for accounting information systems for outpatient and inpatient services at Gebang Medika Maternity Hospital and to analyze the design of accounting information systems for outpatient and inpatient services at Gebang Medika Maternity Hospital and Clinic. The data collection method was carried out by direct observation to the research object, namely the Maternity Hospital and the Gebang Medika Clinic. The data used are primary data. This study uses PIECES analysis and its design uses a web base technology and MySQL for its database. The result of the research is the process of outpatient and inpatient services at this clinic is still using a manual system so that a computerized system is created. The procedure for outpatient and inpatient services at this clinic starts from the patient coming to the clinic then carrying out an examination at the intended polyclinic then being examined and given a copy of the prescription by the doctor. Then a payment receipt will also be given and the patient makes a payment transaction at the cashier and gets a receipt and a copy of the prescription as an introduction to get a medicine. Designing an accounting information system for outpatient and inpatient services is carried out through stages such as: briefly describing outpatient and inpatient service procedures, building a system by describing a database scheme using entity relationship diagrams (ERD), and analyzing patient care systems. outpatient and inpatient care using PIECES analysis and making comparisons with the new system.